Factors Controlling Soil Organic Carbon Stocks with Depth in Eastern Australia. Issue 6 (29th September 2016) - Gray, Jonathan M.; Bishop, Thomas F.A.; Wilson, Brian R.
Abstract : Understanding the potential of soil to store soil organic carbon (SOC) is important for potential climate change mitigation strategies and assessing soil health issues. We examined the factors controlling SOC storage in eastern Australian soils and how these vary with depth. Models were developed using a set of readily interpreted covariates to represent key soil forming factors together with multiple linear regression (MLR) and Cubist piecewise decision tree techniques. Independent validation demonstrated concordance correlation coefficients up to 0.68 for SOC density in near surface layers but progressively decreasing with depth. The results demonstrate the key role of climate (rainfall and maximum temperatures) in controlling SOC stocks, with parent material (lithology) and vegetation cover also being key drivers, while topography and aspect are of lesser influence, at least at this sub‐continental scale. The relative influence of temperature and land use/vegetation cover decreases with depth, while that of parent material increases. The necessity of considering a combination of factors when deriving meaningful estimates of current or projected SOC storage is demonstrated with quantitative estimates of SOC stocks in 45 different climate‐parent material‐vegetation cover regimes. Average SOC stocks in the 0‐ to 30‐cm depth interval range from 16.3 Mg ha ‐1 in dry, highly siliceous parent material environments with low vegetation cover, up to over 145.0 Mg ha ‐1 in wet, mafic parent material environments with high vegetation cover. Results suggest that the proportion of SOC stock in the 30‐ to 100‐cm interval as a proportion of the top 100 cm varies from a low of 41% in wet climates up to a high of 59% in dry climates. Climate appears to be the dominant controller of subsoil SOC storage proportion, with parent material and vegetation cover also having restricted influence.